Strategic Role of Schools in Rural Economic Development - arisman, ari (Journal of Society and Development, 2022)
Schools have a multifaceted role in improving the rural economy. Through education and training, human resource development, innovation, entrepreneurship, community involvement, information networks, poverty alleviation, environment and sustainability, schools can be a catalyst for positive change in the rural economy. The aim of this research is to determine the role of schools in improving the rural economy. The research used qualitative methods, data was obtained from the results of researchers' observations and surveys on the role of schools in improving the rural economy. The research results show that schools make a major contribution to improving the rural economy. Investment in village education is an investment in a future that can provide more prosperity and sustainability.